PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING BEHAVIOR: Studi Kasus Mahasiswa di Kota Sungai Penuh dan Kabupaten Kerinci - Edia Satria (LP2M Universitas Bina Bangsa, 2024)
This study aims: 1. To determine the effect of Shopping Lifestyle on Impulse Buying Behavior in students in Sungai Penuh City partially and how much influence it has. 2. To find out the effect of Fashion Involvement on Impulse Buying Behavior in students in Sungai Penuh City partially and how much influence it has. 3. To find out the effect of Shopping Lifestyle and Fashion investment on Impulse Buying Behavior in students in Sungai Penuh City simultaneously and how much influence it has. The research methodology used is with qualitative descriptive and quantitative descriptive approaches. The results of the study are; 1. Shopping Lifestyle has no effect on Impulse Buying Behavior in students in Sungai Penuh City as evidenced by the calculated value smaller than the ttable value and the magnitude of the effect is only 0.82%. 2. Fashion Involvemen affects Impulse Buying Behavior in students in Sungai Penuh City as evidenced by the calculated value greater than the ttable value and the magnitude of the influence is 6.34%. 3. Simultaneously, Shopping Lifestyle and Fashion Involvement affect Impulse Buying Behavior in students in Sungai Penuh City and the magnitude of the influence is 7.2%.